Human Body: Human Body - Sothonchai, Watcharee; Donkamonkan, Tanakorn; Suanmafai, Paitoon (RATANABUTH JOURNAL, 2024)
“Human Body System” is a book written in prose. Use easy-to-read language with clear illustrations. Make it easy for readers who have basic knowledge in this matter to understand. The first chapter of the book is about cells and tissues. The cell is the structural subunit of living things. Many cells together form tissue. And when many tissues come together to form organs, organs can be formed from different types of tissues. When various organs work together to create a living human body system. In our body it consists of Blood and immune system Growth and development, nervous system, special perception cardiovascular system respiratory system urinary system, digestive system Endocrine system Musculoskeletal system Microorganisms and parasites, reproductive systems, nutrition, degenerative diseases, and tumors are covered with content, pictures, and explanations of processes. and the mechanism of operation of various systems in this body is appropriate This book is suitable for people who have some basic knowledge about body systems or for students who have already learned some basic knowledge about the body. This book is therefore not suitable for elementary school children because when reading it, it will be difficult to understand beyond their age and basic knowledge. Therefore, overall, the book is about the human body system (Human Body) and is beneficial to the general public in understanding the human body system from the book. This book is Makes those who read it understand the workings of various things and take care of their body properly.